Penerapan Akuntansi Lingkungan Terhadap Pengelolaan Limbah Bahan Berbahaya Beracun (B3) Pada PT Master Mat - Ismaya Khoirun Nisa; Dura, Justita (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2024)
This research aims to determine the application of environmental accounting to the management of toxic hazardous waste (B3) at PT Master Mat. Starting from waste processing activities and the impact of implementing environmental accounting. This research uses a descriptive method by collecting data sources through observation and interviews. The research results show that waste management activities have been carried out appropriately. The financial report regarding waste processing at PT Master Mat does not yet present a separate environmental cost report in the Financial Report. Future research is expected to be able to develop populations and other independent variables to obtain more accurate and comprehensive results.